Low-Temperature Hydrotreatment of C4/C5 Fractions Using a Dual-Metal-Loaded Composite Oxide Catalyst - Zhou Du; Renyi Li; Zhenghui Shen; Xiao Hai; Ruqiang Zou (Nanomaterials)
C4 and C5 fractions are significant by-products in the ethylene industry, with considerable research and economic potential when processed through hydrogenation technology to enhance their value. This study explored the development of hydrotreating catalysts using composite oxides as carriers, specifically enhancing low-temperature performance by incorporating electronic promoters and employing specialized surface modification techniques. This approach enabled the synthesis of non-noble metal hydrogenation catalysts supported on Al2O3–TiO2 composite oxides. The catalysts were characterized using various techniques, including X-ray diffraction, N2 adsorption-desorption, scanning electron microscopy, X-ray photoelectron spectroscopy, ammonia temperature-programmed desorption, infrared spectroscopy, and transmission electron microscopy. Mo–Ni/Al2O3–TiO2 catalysts were optimized for low-temperature hydrotreating of C4 and C5 fractions, demonstrating stable performance at inlet temperatures far below those typically required. This finding enables a shift from traditional gas-phase to gas–liquid two-phase reactions, eliminating the need for high-pressure steam in industrial settings. As a result, energy consumption is reduced, and operational stability is significantly improved.